HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN INTERAKSI SOSIAL PADA ANAK USIA DINI DI GRIYA BENOWO INDAH 1 SURABAYA - Jubeda Kasongat; Ressy Mardiyanti; Starry Kireida Kusnadi (PSIKOWIPA (Psikologi Wijaya Putra), 2020)
This study aims to determine whether the relationship between parenting parents withchildren's social interactions. Parenting was the treatment of parents in order to meet the needsand educate children in everyday life. In a family, the presence of parents was very important forthe development of a child's personality, because the family wa the first and foremostenvironment that will later have an influence on several aspects of child development, includingchild discipline. This parenting was divided into 3 types namely authoritarian parenting,democratic parenting and permissive parenting in this study.The research was conducted in thebeautiful Benowo 1 Surabaya, with the research subjects being parents who have children at anearly age (3-4 years), amounting to 32 people. Data collection tool in the form of parentingquestionnaire consisting of 10 items a statement and social interaction questionnaire consistingof 22 items a statement. Data analysis was performed with Pearson's product momentcorrelation statistics technique, with the help of the SPSS for Windows Version 21 program.From the results of the analysis of the research, it was found that the correlation betweenparenting and social interaction of children was 0.516 with sig (2-tailed) value of 0.002.Compared to the significance level of 0.05 (5%), the sig (2-tailed) value is smaller, which meansthere is a relationship between parenting (X) parenting and social interaction (Y) of earlychildhood in Griya Benowo Indah 1 Surabaya . Keywords: Parenting Parenting and Early AgeSocial Interaction.